2018
DOI: 10.1371/journal.pone.0205902
|View full text |Cite
|
Sign up to set email alerts
|

Tyro3/Axl/Mertk-deficient mice develop bone marrow edema which is an early pathological marker in rheumatoid arthritis

Abstract: Rheumatoid arthritis is an auto-immune disease of the synovial joints, hallmarked by chronic inflammation and subsequent progressive tissue destruction. TYRO3, AXL and MER (gene name Mertk) (TAM) receptors are part of a negative feedback signaling system in the immune reaction and mediate efferocytosis thereby tempering the inflammatory process. We have shown that Axl-/- and Mertk-/- mice develop more severe arthritis whereas activating these receptors by overexpressing their ligands Pros1 and Gas6 ameliorates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Axl/Mertk double knockout mice are susceptible to T-cell mediated uveitis, 44 and Tyro3/Axl/Mertk triple knockout mice develop bone marrow edema and macrophage and B-cell and T-cell infiltration, consistent with changes seen in spondyloarthritidies. 45 MERTK is expressed at high levels in the ovaries, prostate, testis, lungs, retinas, and kidneys, and at lower levels in the heart, brain, and skeletal muscle. 46 MERTK is also expressed in macrophages, dendritic cells, natural killer (NK) cells, NKT cells, and platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Axl/Mertk double knockout mice are susceptible to T-cell mediated uveitis, 44 and Tyro3/Axl/Mertk triple knockout mice develop bone marrow edema and macrophage and B-cell and T-cell infiltration, consistent with changes seen in spondyloarthritidies. 45 MERTK is expressed at high levels in the ovaries, prostate, testis, lungs, retinas, and kidneys, and at lower levels in the heart, brain, and skeletal muscle. 46 MERTK is also expressed in macrophages, dendritic cells, natural killer (NK) cells, NKT cells, and platelets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activation of TAM receptors induces, among others, suppressor of cytokine signaling (SOCS) proteins 1 and 3, which reduce production of numerous cytokines [ 9 , 14 , 15 ]. Although we recently showed that Mer and Axl play a protective role in mouse models of RA, the exact function of TAM receptors in RA patients remains largely unknown [ 16 18 ]. TAM receptors can be cleaved from the cell surface, leading to shedding of their soluble ectodomain and consequently a soluble form of the receptor [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the initial report of the triple TAM KO phenotype, a recent work on the same mice quite surprisingly showed that, in comparison with wild types (WT), KO littermates had neither macroscopic nor histological evidence of inflammatory arthritis in ankle joints until the age of 52 weeks [72]. As suggested by the authors, a different phenotype observed in a genotypically identical animal model may be justified by changes in the interplay between genetic and environmental factors, including, for example, improved cleanliness of facilities and modifications of the microbiota.…”
Section: Tam Receptors Implications In Rheumatoid Arthritismentioning
confidence: 99%
“…The latter, in particular, could represent an exciting link with RA as the dysbiosis seems to be a promoter of inflammatory arthritis [73]. Despite not showing clinically evident arthritis, however, both adolescent and adult TAM -/mice had significantly more marked bone marrow oedema, which is an early sign of arthritis [72].…”
Section: Tam Receptors Implications In Rheumatoid Arthritismentioning
confidence: 99%